(untitled) (Journal of Informatics and Mathematical Sciences, 2013)
We define an action set of a regular curve not passing origin using a normed projection. If α(t) is a regular curve not passing origin, then the curve β(t)=α(t)\|α(t)\| is on unit sphere. β(t) is called normed projection of α(t) 3. Every point b(t)β(t) defines an orthogonal matrix using Cayley’s Formula. So we define an action set R_α (t)SO(3) of α(t). We study in this article some important relations α(t) and R_α (P), orbit of point PR^3. At the end we give some applications in Matlab.